The Relationship between BMI and the Incidence of Stunting in Infants Aged 2-5 Years at the Nuangan Boltim Health Center - Sherly Manopo; Anik Purwati; Maria Veronika Widiatrilupi (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2025)
Stunting is a condition characterized by a height or body length shorter than expected for a child's age, commonly referred to as being underdeveloped or dwarfed. It is a chronic nutritional problem in toddlers, influenced by various factors including socioeconomic conditions, maternal nutrition during pregnancy, birth weight and length, frequent illnesses in infants, and inadequate nutritional intake during infancy. Stunting can have long-term effects on physical and cognitive development, which makes its prevention crucial. This research aims to investigate the relationship between Body Mass Index (BMI) and the incidence of stunting in children aged 2-5 years at the Nuangan Health Center. The study employed a quantitative correlation approach with a cross-sectional design to assess this relationship. A total of 20 respondents, selected using purposive sampling, participated in the study. The research utilized a weighing scale and measuring tape as instruments for data collection. Data analysis was conducted using the Chi-Square test, which helped determine the significance of the relationship between BMI and stunting occurrence. The results revealed a statistically significant relationship (Sig = 0.027 < 0.05), suggesting that BMI is a key factor influencing the occurrence of stunting in toddlers at the Nuangan Health Center. This finding underscores the importance of monitoring BMI and addressing nutritional issues early in childhood to prevent stunting and its potential consequences on growth and development. The study highlights the need for health interventions focusing on improving maternal and infant nutrition, as well as promoting better health practices to mitigate the risk of stunting in young children.